Antibacterial and antifungal activity of curcumin and methylene blue associated with laser on bacterial and fungal strains - Brenda Ellen Meneses Cardoso; Ana Andreza Albuquerque Medeiros; Matheus Lopes Martins; André Luca Araujo de Sousa; Nathanael dos Santos Alves; Leiz Maria Costa Veras; Alyne Rodrigues Araújo; Antonione Santos Bezerra Pinto (Hospital de Clínicas de Itajubá, 2023)
Objective: To analyze the effect of methylene blue and 10% curcumin in fungi and bacteria through an in vitro study using photodynamic therapy (PDT). Methods: Curcumin and methylene blue were photosensitized by a Photon Lase III laser applied for 90 s in a dark environment within a laminar flow chamber. Enterococcus faecalis and Candida albicans strains were cultured and standardized. Then, a minimum inhibitory concentration (MIC) assay was conducted for these photosensitizers, with concentration variations and incubation to evaluate their antimicrobial activity. Results: With PDT, Curcumin had significant antibacterial activity against E. faecalis (MIC = 250 µg/mL). In contrast, methylene blue had antibacterial activity against E. faecalis (MIC < 12.5 µg/mL with PDT) and antifungal activity against C. albicans (MIC <12.5 µg/mL with or without PDT). Both agents showed greater efficacy in the presence of the laser. The results suggest that curcumin and methylene blue associated with laser may effectively treat microbial infections. Conclusion: Further research is needed to evaluate the efficacy and safety of using these agents in animal and human models and their effectiveness against different bacterial and fungal strains.